Exploring the Potentiality of Ecotourism in Betana Simsar Community Forest, Koshi Province, Nepal - Rajbanshi, Bina Kumari; Acharya, Keshav Raj (FORESTRY: Journal of Institute of Forestry, Nepal, 2023)
The Government of Nepal has focused on ecotourism activities within community forests; but not all community forests are equally potential for ecotourism. This paper mainly focuses on available facilities and services regarding ecotourism development; and tries to analyse local people’s perception of ecotourism promotion as well as visitor’s satisfaction in the Betana Simsar Community Forest of Morang district in Koshi province, eastern Nepal to explore the potentiality of ecotourism. This research was based mainly on household survey (n=53), visitor’s interviews (n=96), key informant survey (n=10) and observation of available infrastructure related to ecotourism development. The study revealed that rich biodiversity and natural scenery of the wetland have attracted more than four million visitors annually. The income received from the tourism has not only supported management of the community forest but also provided employment to eight local people and supported local livelihoods. Two third of the visitors were found satisfied with the available facilities and natural beauty of the area. These facts show the opportunities for ecotourism development in Betana Simsar community forest; however, lack of institutional collaboration among different agencies has been identified major limitation for converting this potentiality into the reality.